Essential self-conjugacy of operators connected with the Cauchy, problem for the wave equation - Orochko , Yu. B. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A sufficient Hartman-Ismagilov type condition for the essential self-adjointness of a one-parameter family of unbounded operators that arise in the solution of a Cauchy problem for the wave equation is established. An analog of this result is stated for unbounded integral operators.